Aberrant Functional Network Connectivity as a Biomarker of Generalized Anxiety Disorder - Qiao, Jianping; Li, Anning; Cao, Chongfeng; Wang, Zhishun; Sun, Jiande; Xu, Guangrun (Frontiers in Human Neuroscience, 2017)
Neural disruptions during emotion regulation are common of generalized anxiety disorder (GAD). Identifying distinct functional and effective connectivity patterns in GAD may provide biomarkers for their diagnoses. This study aims to investigate the differences of features of brain network connectivity between GAD patients and healthy controls, and to assess whether those differences can serve as biomarkers to distinguish GAD from controls. Independent component analysis with hierarchical partner matching (HPM-ICA) was conducted on resting-state functional magnetic resonance imaging data collected from 20 GAD patients with medicine free and 20 matched healthy controls, identifying nine highly reproducible and significantly different functional brain connectivity patterns across diagnostic groups. We then utilized granger causality (GC) to study the effective connectivity between the regions that identified by HPM-ICA. The linear discriminant analysis was finally used to distinguish GAD from controls with these measures of neural connectivity. The GAD patients showed stronger functional connectivity in amygdala, insula, putamen, thalamus and posterior cingulate cortex (PCC), but weaker in frontal and temporal cortex compared with controls. Besides, the effective connectivity in GAD was decreased from the cortex to amygdala and basal ganglia. Applying the ICA and GC features to the classifier led to a classification accuracy of 87.5%, with a sensitivity of 90.0% and a specificity of 85.0%. These findings suggest that the presence of emotion dysregulation circuits may contribute to the pathophysiology of GAD, and these aberrant brain features may serve as robust brain biomarkers for GAD.